A Randomized Trial of Multiple-Patient Simulation Preparation to Improve Novice Nurses' Competence and Self-Efficacy. Issue 3 (May 2020) - Franklin, Ashley E.; Sideras, Stephanie; Dodd, Caitlin; Hutson, Jeremy
Abstract: AIM: The purpose of the study was to determine best practices for multiple-patient simulation (MPS) preparation and frequency to improve behavioral performance in nursing students. BACKGROUND: MPS provides a safe environment for novice nurses to practice priority setting, delegation, and multitasking, but evidence for best practices is needed. METHOD: A multisite, blinded, randomized trial was conducted to evaluate the effect of three simulation preparation methods (expert modeling, voice-over PowerPoint, and reading assignments) on students' competence and self-efficacy for providing care to multiple patients in the simulation lab. Participants ( n = 73) were enrolled in capstone clinical courses at two schools of nursing. RESULTS: Though there was no difference in raw change in competence score among the study groups, there was a statistically significant difference in pretest and posttest scores. The change in self-efficacy did not correlate with the change in competence. CONCLUSION: These findings will help educators understand how novice nurses benefit from repeated MPS activities.